Conversion of rice straw to monomeric phenols under supercritical methanol and ethanol. (July 2015) - Singh, Rawel; Srivastava, Vartika; Chaudhary, Kajal; Gupta, Piyush; Prakash, Aditya; Balagurumurthy, Bhavya; Bhaskar, Thallada
Highlights: Liquefaction of rice straw without any pretreatment is successfully performed. High liquid product yield observed (47 wt%). Ethanol gave higher yield of liquid product. FTIR and NMR showed presence of monomeric phenols. GC–MS confirmed phenol and guaiacol derivatives as major products. Abstract: Hydrothermal liquefaction of rice straw has been carried out using various organic solvents (CH3 OH, C2 H5 OH) at different temperatures (250, 280 and 300 °C) and residence times (15, 30 and 60 min) to understand the effect of solvent and various reaction parameters on product distribution. Maximum liquid product yield (47.52 wt%) was observed using ethanol at 300 °C and 15 min reaction time. FTIR and NMR ( 1 H and 13 C) of liquid product indicate that lignin in rice straw was converted to various monomeric phenols. GC–MS of the liquid product showed the presence of various phenol and guaiacol derivatives. Main compounds observed in liquid product were phenol, 4-ethylphenol, 4-ethyl-2-methoxyphenol (4-ethylguaiacol), 2, 6-dimethoxyphenol (syringol), 2-isopropyl-5-methylphenol (thymol). Powder XRD and SEM of bio-residue showed that rice straw was decomposed to low molecular weight monomeric phenols.